Epistolary narratives in ancient Greek literature - Hodkinson, Owen, 1979-; Rosenmeyer, Patricia A.; Bracke, Evelien (Mnemosyne, bibliotheca classica Batava. Supplementum, 2013)
Epistolary Narratives presents detailed literary readings of a wide range of Greek literary letter collections across a range of genres, cultural backgrounds, and time periods, leading collectively towards a better appreciation of Greek epistolary collections as a unique literary phenomenon.